Application of biopolymers derived from seaweed and their use in dentistry: Aplikasi biopolimer dari rumput laut dan penggunaannya dalam bidang kedokteran gigi - Alda; Nur Mutiara Rezky; Annisa Rahmayani; Lenni Indriani (Makassar Dental Journal, 2026)
The use of synthetic materials in dentistry often leads to problems with medical waste that is difficult to degrade and the risk of infection due to suboptimal mechanical properties and biocompatibility. Acrylic resin, for example, is prone to fracture and can become a breeding ground for microorganisms that cause denture stomatitis. Furthermore, the use of denture adhesives can cause mucosal irritation and increase the risk of infection. This article evaluates the potential of seaweed biopolymers as an environmentally friendly, biocompatible, and multifunctional alternative material in dentistry. Seaweed biopoly-mers are expected to address waste issues and support clinical applications such as dental impression materials, tissue scaffolds, and drug delivery sys-tems effectively and safely. Consequently, the use of seaweed biopolymers can promote more sustainable and innovative dental practices. It is conclu-ded that seaweed biopolymers are environmentally friendly, biocompatible, and multifunctional alternative material for dentistry. Further research is required to optimise their clinical applications